Evaluation of the Biological Efficiency of Greater Wax Moth Larvae (Galleria mellonella) in the Biodegradation of Polystyrene under Laboratory Conditions. (Al-Farooq Journal of Sciences, 2026)
This laboratory study aimed to evaluate the degradative capacity and bio-efficiency of greater wax moth larvae (Galleria mellonella), collected locally from apiaries in the Al-Zahim region, Libya, against expanded polystyrene (Styrofoam), a significant environmental threat. Following natural rearing and feeding until reaching the appropriate size, 100 homogeneous larvae were isolated and subjected to forced starvation for 48 hours. The larvae were then randomly divided into two equal groups (n = 50 per group): an experimental group provided with a standard polystyrene piece (5cm x 5cm) as the sole food source, and a control group maintained on their standard diet of natural beeswax. The results demonstrated high mechanical and behavioral efficiency of the larvae in penetrating and disintegrating the polystyrene, creating coalescing holes within the first 12 hours of exposure. However, statistical survival analysis using the Kaplan-Meier method and the Log-Rank test revealed a statistically significant difference (p = .000) between the two groups during the 7-day digital monitoring period. The polystyrene group experienced a sharp decline and mass mortality of 94%, with a mean survival time of 4.22 days (95% CI: 3.82–4.63 days) and a median survival time of 4.00 days due to bio-stress and chemical nutritional deprivation. Conversely, the control group maintained stability with a survival rate of 92%. The study proved that the larvae's chewing of polystyrene is an obligatory mechanical behavior driven by forced hunger rather than a sustainable nutrient, which warrants directing future research toward extracting the intestinal enzymes responsible for degradation without biologically stressing the insect
Keywords: Galleria mellonella, bio-degradation, polystyrene, Libya